Automatic controller using Programmable Logic Controller (PLC) for Marker Pen Assembly Machine / Ahmad Mizan Md. Yusof - Md. Yusof, Ahmad Mizan (1994)
This project is to design and develop an Automatic Controller using Programmable Logic Controller (PLC) for Marker Pen Assembly Machine. The marker pen consists of five parts barrel, ink pad, felt tip, rear cap and front cap The assembly process divided into four stages sorting, feeding, indexing and insertion. The machine is expected to assemble 3,600 marker pens per hour The PLC is used to transmit and process the electrical signals. A software routine known as ladder diagram is developed and used in the PLC to control the operation of assembly machine automatically.